1560 Cerbe Deni̇z Savaşi - Köse, Sevilay (The Journal of Social Sciences, 2025)
Djerba Island, which had been a refuge for famous pirates since the second half of the 16th century, had an important position for the Mediterranean. Especially when Turgut Pasha, the Beylerbeyi of Tripolitania, took Djerba Island under his control, the Christian world's interest in the island increased. The Crusader troops formed to capture Djerba managed to capture the island and built a castle on the island despite the disagreement between the commanders, bad weather conditions, epidemics and deserters. Upon this news, the Ottoman navy under the command of Piyale Pasha moved towards the island of Djerba. The Ottoman fleet, which was outnumbered, defeated the Crusader fleet off the coast of Djerba. While some of the Crusaders fled, some of them took refuge in the castle of Djerba. The Crusaders were besieged by sea and land for two months. The Ottoman navy forced the Crusaders to surrender by attacking the wells in the castle. In return for the surrender of the Crusaders, their lives were spared and the island of Djerba was annexed to Tripolitania under the Ottoman Empire. This study focuses on the conquest of Djerba by the Ottoman navy, which was an important centre of refuge for Turkish pirates and the domination of the Central Mediterranean.
Keywords: Djerba -- Empire ottoman; Invasions chrétiennes -- Djerba -- 1560

Prigionia e riscatto: il capitano Gerolamo Roccabruna e la spedizione di Gerba del 1560 - Franca, Barbacovi (Studi trentini. Storia, 2020)
Keywords: Invasions chrétiennes -- Djerba -- 1560

A Djerba, le mausolée des martyrs ottomans du siège de 1560 - Bourial, Hatem (Webdo, 2017)
Ce mausolée est minuscule, peu connu et n’a été restauré que depuis quelques années. Pourtant, il témoigne d’un épisode historique de première importance. En février 1560, les soldats de la flotte espagnole s’étaient en effet emparés du borj Ghazi Mustapha après un assaut qui avait surpris la garnison qui se trouvait sur place. Les Espagnols qui en ce temps croisaient le fer avec les Turcs pour la domination de la Méditerranée avaient ainsi marqué un point dans une période des plus troublées. Se réorganisant rapidement, faisant appel à des renforts, les Ottomans allaient vite reprendre le fort disputé. Les escarmouches dureront de mai à juillet et s’achèveront par la libration du fort principal de Djerba. Une modeste plaque et un mausolée regroupant quelques tombes rappellent cet épisode de notre histoire et les clameurs des vaisseaux de guerre en Méditerranée. C’est aussi la mémoire de Khereddine, Barberousse et Dragut qui est évoquée par ce mausolée, l’un des rares qui témoignent des luttes entre Ottomans et Espagnols pour le contrôle des côtes tunisiennes.
Keywords: Invasions chrétiennes -- Djerba -- 1560

Dire le désastre militaire, Los Gelves (Djerba), 1560 - Perez, Béatrice (Écrire l’histoire des catastrophes, 2016)
Keywords: Invasions chrétiennes -- Djerba -- 1560

1560 Cerbe Deniz Zaferi Ve Cerbe Kalesinin Fethi - Önalp, Ertuğrul (Ankara Üniversitesi Osmanlı Tarihi Araştırma ve Uygulama Merkezi Dergisi, 2001)
[The sea victory of Jerba and the capture of the castle of Jerba].
Keywords: Invasions chrétiennes -- Djerba -- 1560

1560 Cerbe Deniz Savaşinin Türk Ve İspanyol Tarihindeki Yeri - Akinci, Tunç (Université d’Ankara, 2008)
Keywords: Invasions chrétiennes -- Djerba -- 1560

The last crusaders: the hundred-year battle for the centre of the world - Rogerson, Barnaby (Overlook Press, 2010)
The Crusades were the bridge between medieval and modern history, between feudalism and colonialism. In many ways, the little explored later Crusades were the most significant of them all, for they made the crisis truly global. "The Last Crusaders" is about the period's last great conflict between East and West, and the titanic contest between Habsburg-led Christendom and the Ottoman Empire in the fifteenth and sixteenth centuries.It focuses not on the more famous Crusades from 1095 and 1291 but on a later series of clashes between various Christian and Muslim forces in and around the Mediterranean, beginning with Portugal's capture of the city of Ceuta in 1415 and ending with the battles at Lepanto in 1571 and Alccer Quibir in 1578. From the great naval campaigns and the ferocious struggle to dominate the North African shore, the conflict spread out along trade routes, consuming nations and cultures, destroying dynasties, and spawning the first colonial empires in South America and the Indian Ocean. The author presents not only the exploits of both Christians and Muslims on the battlefield but also their shifting alliances and internal struggles. He also explores how military technologies and the expansion of trade and exploration helped shape the conflicts. This book provides a vibrant and well-organized account of this tumultuous, lesser-known period of history
Keywords: Invasions chrétiennes -- Djerba -- 1560; Tour des crânes (Djerba)

The Norman Kingdom of Africa and the Medieval Mediterranean - King, Matt (University of Minnesota, 2018)
During the twelfth century, the Mediterranean Sea contained a complex array of economic, political, military, religious, and social networks. My dissertation explores the relationship of two dynasties that were at the center of these networks: the Norman lords of Sicily and the Zirid emirs of Ifriqiya (roughly modern-day Tunisia, eastern Algeria, and western Libya) in the years leading up to the Norman conquest of Zirid lands and the formation of the Norman Kingdom of Africa (1148-1160). Previous scholarship, particularly work written by French colonial historians, has emphasized the triumph of the Christian Normans over their Muslim foes and disregarded the agency of the Zirids. I show that the medieval sources tell a different story. Latin and Arabic texts attest to the importance of the Zirid emirs of Ifriqiya to larger networks in the Mediterranean. In 1123, for example, the Zirid emir al-Hasan ibn ‘Ali united a group of Arab and Berber (indigenous North African) tribes to defeat the navy of the Norman lord Roger II. Several years later, al-Hasan ibn ‘Ali formed an alliance with the Almoravids of Morocco to raid cities along the coast of Sicily. Zirid power in Ifriqiya only waned in the wake of a decade-long drought, which allowed the opportunistic Normans to seize Zirid lands. The Normans under Roger II and his son William I ruled the coastline of Ifriqiya for twelve years, during which time they made small changes to its society that favored Christians over Muslims while occasionally proclaiming themselves “King of Africa.” Arabic chroniclers writing about the Norman conquest of Ifriqiya did not acknowledge the legitimacy of the Normans’ kingship in Ifriqiya and instead presented the Normans as one prong of a Mediterranean-wide “Frankish” assault upon the lands of Islam, one that warranted jihad on all fronts.
Keywords: Invasions chrétiennes -- Djerba -- 1560

Para una biografía de Lope de Figueroa : notas críticas y nuevas aportaciones. Parte primera: hasta la jornada de Djerba y el final de su cautiverio por los Turcos (1564) - Leonardi, Salvatore (Revista de historia militar, 2013)
Keywords: Invasions chrétiennes -- Djerba -- 1560

1560 Cerbe Deniz Savaşının Türk ve İspanyol tarihindeki yeri - Önalp, Ertuğrul (Ankara Üniversitesi, 2008)
Spain and Venice felt more and more threatened by the Ottomans and their corsair allies after losing against Barbarossa Hayreddin's Ottoman fleet at the Battle of Preveza in 1538 and the disastrous expedition of Emperor Charles V against Barbarossa in Algiers in 1541.Especially when Piyale Pasha had captured the Balearic Islands and together with Turgut Reis raided the Mediterranean coasts of Spain in 1558. Taking advantage of the piece made between Spain and France ;the initiative came from Maltese Knights who appealed to King Philip II of Spain to organize an expedition to retake Tripoli from Turgut Reis, who had captured the city from the Maltese Knights in August 1551 and had subsequently been made Bey (Governor) of Tripoli by Sultan Suleiman the Magnificent.The naval Battle of Djerba took place in May 1560 near the island of Djerba, Tunisia. It is believed by most reputable historians that the fleet assembled by the allied Christian powers in 1560 consisted of between 50 and 60 galleys and between 40 and 60 smaller craft. For instance , the official historian of the Knights of St John Giacomo Bosio, writes that there were 54 galleys. Fernand Braudel also mentions about 54 warships plus thirty-six supply vessels. Carmel Testa who had access to the archives of the Knights of St. John made more accurate listings. He lists precisely 54 galleys, 7 brigs, 17 frigates, 2 galleons, 28 merchant vessels and 12 small ships. These ships and their supplies were supplied by a coalition that consisted of Genoa, Naples, Sicily, Florence the Papal States, and the Knights of Saint John. Giovanni Andrea Doria, nephew of the Genoese admiral Andrea Doria, took the command of the fleet which assembles in Mesina. The fleet first sailed to Malta, where bad weather conditions and the hard sea forced it to remain for two months. Around 2,000 men were lost there, due to bad conditions and contagious diseases.Finally the fleet set sail for Tripoli on 10 February, 1560. Unfortunately we do not know the exact number of soldiers aboard. Braudel gives 10,000-12,000; Testa 14,000; considering the number of men a sixteenth century galley could carry, old figures like 20.000 are completely exaggerations.The expedition came to shore near to Tripoli but the lost of too many soldiers and the bad condition of the remaining soldiers changed the objectives. They decided to take Djerba first to use it as a command centre for the operation that was to made to Tripoli. Then the expedition returned to Djerba which they overran quickly. The Viceroy of Sicily, Don Juan de la Cerda, Duke of Medina Coeli, ordered the fort in the island to be strengthened.By that time Piyale Pasha was ordered to patrol in the Mediterranean and to sieged a small island of Malta, he learnt a Christian fleet occupied Djerba to occupy later Tripoli. The Turkish fleet changed it?s course and head to Djerba after taking necessary precautions. The fleet arrived at Djerba on 11 May 1560. Since the Christian forces did not expect it to come before July it was a complete surprise for them. With the help of the strong winds, Piyale Pasha had closed the Gap between Istanbul and Djerba in less then a month.The battle was over in a matter of hours, with about half the Christian galleys captured or sunk. Anderson gives the total number of Christian casualties as 18,000 but Guilmartin more conservatively puts the losses at about 9,000 of which about two-thirds would have been oarsmen.Giovanni Andrea Doria the commander of the fleet managed to escape in a small vessel and the remaining forces took refuge in the fort that they had strengthened just days earlier, which was soon attacked by the combined forces of Piyale Pasha and Turgut Reis. The garrison surrendered after a siege of three months and Piyale Pasha took the prisoners back to Istanbul, including the Spanish commander D. Alvaro de Sande, who had taken command of the Christian forces after Doria had escaped. The accounts of the final days of the besieged garrison are irreconcilable.The victory in the Battle of Djerba represented the apex of Ottoman naval domination in the Mediterranean. Soon The Ottomans made an unsuccessful effort on Malta in 1565, the new base of Saint Jean Knights who were expelled from Rodas. Although the Ottomans had captured Cyprus from Venice in 1571 the legend of the invincible Ottoman fleet continued until the Battle of Lepanto in 1571 where the Turkish naval forces were destroyed by the Christian fleet.Shortly after The Ottomans were able to build another large fleet in less than a year after Lepanto, and recaptured Tunis from the Spaniards and their Hafsid vassals in 1574.
Keywords: Invasions chrétiennes -- Djerba -- 1560

Dire la débâcle militaire, Los Gelves (Djerba, 1560). Quand l’humiliation morale blesse l’âme - Perez, Béatrice (L'élégie du désastre: de l'archive à l'histoire, 2019)
Keywords: Invasions chrétiennes -- Djerba -- 1560